Analys of student contraints in completing integral topics - Nia Maharani (PendIPA Journal of Science Education, 2023)
Mathematics is one of the compulsory subjects in semester 1 of the Computer Systems major. In this course there is an integral topic. Based on interviews conducted by researchers with semester 1 students from class of 2022 at the beginning of the study, the questions on integrals were difficult to solve. This study aims to analyze qualitatively with the help of quantitative data in the form of tests given to 40 students to review what obstacles students have experienced so far in solving integral problems. This study gave the results of student constraints, including the lack of understanding of students in understanding the basic concept of the integral itself. Integral is anti-derivative so this is the initial basis for understanding integrals. The next obstacle is the lack of students' mathematical skills, namely the operation to equalize the denominator for fractions and the lack of accuracy in calculations. The cause of the constraints mentioned above is the lack of independent problem exercises carried out by students outside of mathematics lecture hours so that students' mastery of concepts is lacking. The development of learning methods later is expected to minimize the above constraints.